Review on the Digitalization and Intelligent Development of Physical Simulation Methods for Hydraulic Fracturing - Bing HOU; Zhihao LIAO; Zhuang ZHANG; Jialun LUO; Yiwen JU; Wen WANG (Liaoning Shiyou Huagong Daxue xuebao, 2025)
Traditional physical simulation method of hydraulic fracturing has certain limitations in quantitatively studying fracture morphology and dynamically monitoring fracture propagation paths. It is challenging to quantitatively evaluate the dynamic processes of fracture initiation and propagation. Therefore, there is an urgent need to develop digital and intelligent technologies to enhance the accuracy of hydraulic fracturing physical simulation methods. Systematically investigated the method principle, research status and development direction of digital core reconstruction, acoustic emission positioning and distributed optical fiber monitoring, explored the data acquisition, fracture reconstruction and data interpretation in the process of multi⁃method joint monitoring experiment, and clarified the sample preparation, method combination and application scope in hydraulic fracturing physical simulation. The characteristics of non⁃plane, asymmetrical and unbalanced initiation and propagation of true triaxial hydraulic fracturing physical simulation are pointed out and outlooks are presented with the aim of helping researchers deeply understand the dynamic process of complex fracture expansion. Digital and intelligent hydraulic fracturing physical simulation methods are the future research trend. The research results can be used as reference for the development of hydraulic fracturing physical simulation technology, experimental scheme design.